Epistemic Rhetoric in Virtual Reality Interactive Factual Narratives - Fisher, Joshua A. (Frontiers in Virtual Reality, 2022)
The turn to Interactive Digital Narratives to understand complexity offers a new model for creating, developing, and maintaining knowledge. At the same time, storytellers have turned their attention to Virtual Reality (VR). The confluence of these trends draws attention to how non-fiction practitioners can use the technical and aesthetic affordances of VR to create knowledge about complex subjects through the IDN form. This article explores the epistemic rhetorical nature of using narrative discourse in VR to create knowledge about a non-fiction subject. The IDN community has not addressed this rhetorical aspect in their proposed epistemological process. Clarifying the epistemic rhetorical aspect inherent in producing knowledge on complex subjects through IDN provides insights into practitioners’ persuasive and political design and development choices. These intentional choices, in turn, impact the kind of knowledge produced. This rhetorical approach to knowledge production can be grounded in a Neo-sophist epistemic tradition wherein aesthetic choices are used rhetorically. I will present and discuss the Sophist rhetorical tactics of antithesis, the rhetoric of the possible; enargia, the rhetoric of vivid details; kairos, the rhetoric of opportune timing; and mêtis, the rhetoric of the body. Their implementation by practitioners, how these aesthetic choices rhetorically create knowledge in the Systems-Process-Product model is presented. The article clarifies these rhetorical processes and choices and analyzes the 2021 Tribeca Film Festival’s Best Immersive Narrative, The Changing Same: An American Pilgrimage: Episode 1. This VR factual IDN allows interactors to experience historical moments of racial injustice in the United States. The production team was interviewed about how they used the technical and aesthetic qualities of VR and IDN rhetorically to produce knowledge about the complex and violent history of racial injustice in the United States. Their responses indicate their active use of epistemic rhetorical tactics that capitalize on the technical and aesthetic affordances of VR and IDN to create knowledge.